Urgensi Lemah Lembut Dalam Metode Dakwah Rasulullah SAW - Kurniawan, Setyo (Al Ashriyyah, 2022)
Rasulullah SAW is the best example of preaching, he is a human being who has tenderness towards all those whom he preaches. Islam is like pearls and softness like a wrap. When the wrapper is no longer beautiful and dirty, then don't ever expect humans to open it. just open it reluctantly let alone accept the pearl in it. Someone when preaching must pay attention to this noble character, must not be careless and act harshly in preaching. Because of acting harshly in preaching, the Prophet never did it at all. Allah Ta'ala has explained the basic methods of preaching, one of which is wisdom and gentleness.